Provisional Public Health Service Inter-Agency Recommendations for Screening Donated Blood and Plasma for Antibody to the Virus Causing Acquired Immunodeficiency Syndrome - สำนักระบาดวิทยา (รายงานการเฝ้าระวังทางระบาดวิทยาประจำสัปดาห์, 2025)